Investigation of therapeutic drug monitoring of tacrolimus in different age groups: results from a turkish nationwide study - Caglayan, Murat; Gonel, Ataman; Celik, Osman; Sozuer, Abdulvahit; Ulgu, Mustafa Mahir; Ata, Naim; Birinci, Suayip (BENTHAM SCIENCE PUBL LTD, 2023)
Background The blood level of tacrolimus (TAC) used for post-transplant immunosuppression should be within the therapeutic index. Geriatric individuals may be at risk of organ rejection because, in this age group, routine drug use is usually disrupted, and the bioavailability of aging-related drugs is decreased. Objective The aim of this study was to analyze the age-related variability of blood TAC levels in patients in Turkey. Methods In this study, 697,616 patients who underwent TAC measurement in the laboratories of public, private, and university hospitals between 2018 and 2020 were identified from the Health-net database of the Ministry of Health. The results of patients aged & GE;65 years were compared with those of patients aged Results The study included 697,616 patients. The mean TAC concentration was 7.2 & PLUSMN; 6.25 ng/mL for all the patients, 7.13 & PLUSMN; 6.7 ng/mL for the female patients, and 7.24 & PLUSMN; 5.96 ng/mL for the male patients. A statistically significant difference in TAC concentration was found between men and women in the general population. Groups aged & GE;65 years were compared among themselves. A statistically significant decrease in TAC concentration was found only in the age group of 75-79 years (5.63 & PLUSMN; 4.09 ng/mL) of women compared with the men. In all other age groups, the TAC levels of the men were lower. Conclusion The proportion of patients with TAC concentrations lower than the therapeutic index was higher in the groups aged & GE;65 years. Thus, patients aged & GE;65 years may be at risk of organ rejection, as optimum immunosuppression cannot be achieved. In these patients, more frequent drug monitoring and providing training to ensure the compliance of the patient and the patient's relatives in the use of TAC may be recommended.
Keywords: optimum immunosuppression; drug monitoring; drug analysis; big data; elderly; Tacrolimus